EFFECT OF BIO-STIMULATORS ON PRODUCTION OF COWPEA SEED FOR FOOD SECURITY AND WEALTH CREATION IN JUJA, KENYA - Ilukol, Judith Oyoo (Journal of Experimental Sciences, 2016)
A study was done to evaluate the effect of bio-stimulators on seed production of cowpea crop in Juja, Kenya during short rains season 2014-15. Bio-stimulators are plant and animal derived substances that trigger plant processes when applied to the plants at very low concentrations. They contain amino acids, low molecular weight polypeptides, vitamins, enzymes, hormones, sugars, betaines and antioxidants. Drought causes slow rate of the majority of plant growth and development processes leading to discontinuation of cell growth, stomatal closures, increased abscisic acid and proline, drop in cytokinins levels, reduced protein synthesis and reduced activity of nitrate reductase leading to retarded growth and plant senescence. In reducing the impact of the water stress therefore, cytokinins in bio-stimulators promote growth and slow down plant senescence. Parameters investigated were germination rate, days to flowering and pod formation, number of seeds per pod, length of pods, total number of pods and weight of seeds. Results on the effect of bio-stimulators on cowpea seed production are discussed.